Safety and use of complementary and alternative medicine in Norway during the first wave of the COVID-19 pandemic using an adapted version of the I-CAM-Q; a cross-sectional survey - Agnete Egilsdatter Kristoffersen; Miek C. Jong; Johanna Hök Nordberg; Esther T. van der Werf; Trine Stub (BMC Complementary Medicine and Therapies, 2022)
Abstract Background The COVID-19 pandemic lockdown has had a profound impact on physical and mental well-being throughout the world. Previous studies have revealed that complementary and alternative medicine (CAM) is frequently used for, and can be potential beneficial for strengthening physical mental resilience. The aims of this study were therefore to determine the prevalence and reasons for use of CAM during the first wave of the COVID-19 pandemic among a representative sample of the Norwegian population, and further determine self-reported effects and adverse effects of the CAM modalities used. Methods Computer assisted telephone interviews using a COVID-adapted I-CAM-Q questionnaire were conducted with 1008 randomly selected Norwegians aged 16 and above using multistage sampling during April and May 2020 applying age and sex quotas for each area. Frequencies, Pearson’s chi-square tests, Fisher exact tests, and independent sample t-test were used to identify the users of CAM, what they used, why they used it and whether they experienced effect and/or adverse effects of the modalities used, and further to describe differences in sociodemographic factors associated with CAM use. Cronbach's alpha tests were used to test for internal consistency in the different groups of CAM. Significance level was set to p < 0.05. Results The study revealed that two thirds of the respondents (67%) had used CAM within the first 3 months of the COVID-19 pandemic, in particular CAM modalities that did not involve a provider. Most used were natural remedies and dietary supplement (57%, mainly vitamins and minerals), but self-help practices like yoga and meditation were also widely used (24%). Women used CAM modalities significantly more than men (77% vs. 58%). Most of the respondents found the modalities they used beneficial, and few reported adverse effects of the treatments. Conclusions A large proportion of the Norwegian population used CAM during the first wave of the COVID-19 pandemic with high satisfaction and few reported adverse effects. CAM was rarely used to prevent or treat COVID-19, but rather to treat a long-term health condition, and to improve well-being.